The Influence Of Work Environment And Facilities On Employee Performance At The Central Industrial Smokehouse Indah Wonosari Bonang Demak - Syamsul Hadi; Y.R. Satato; Dwi Puji Kurniasari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This research was conducted at the Central Industrial Smokehouse Indah Wonosari Bonang Demak, with the research objectives being (1) to determine the influence of the work environment on employee performance at the Central Industrial Smokehouse Indah Wonosari Bonang Demak, (2) to determine the influence of work facilities on employee performance at the Central Industrial Smokehouse Indah Wonosari Bonang Demak, (3) to determine the combined influence of the work environment and work facilities on employee performance at the Central Industrial Smokehouse Indah Wonosari Bonang Demak, (4) to identify which variable has the most significant influence on employee performance at the Central Industrial Smokehouse Indah Wonosari Bonang Demak. In this research, a quantitative survey research method with a field approach was employed. The population of this study was all employees working at the Central Industrial Smokehouse Indah Wonosari Bonang Demak, totaling 61 employees. Since the population is less than 100, all employees (61) were included as the sample. The research results indicate that: (1) The work environment (X1) significantly influences employee performance (Y) at the Central Industrial Smokehouse Indah Wonosari Bonang Demak. (2) Facilities (X2) significantly influence employee performance (Y) at the Central Industrial Smokehouse Indah Wonosari Bonang Demak. (3) The combined influence of the work environment (X1) and facilities (X2) significantly affects employee performance (Y) at the Central Industrial Smokehouse Indah Wonosari Bonang Demak. (4) The variable that has the most significant influence on employee performance is the work environment variable.